2012
DOI: 10.1016/j.expneurol.2012.01.027
|View full text |Cite
|
Sign up to set email alerts
|

In vivo intermittent hypoxia elicits enhanced expansion and neuronal differentiation in cultured neural progenitors

Abstract: In vitro exposure of neural progenitor cell (NPC) populations to reduced O2 (e.g. 3% versus 20%) can increase their proliferation, survival and neuronal differentiation. Our objective was to determine if an acute (<1 hr), in vivo exposure to intermittent hypoxia (AIH) alters expansion and/or differentiation of subsequent in vitro cultures of NPC from the subventricular zone (SVZ). Neonatal C57BL/6 mice (postnatal day 4) were exposed to an AIH paradigm (20×1 minute; alternating 21% and 10% O2). Immediately afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
2
21
0
1
Order By: Relevance
“…Pax6 expression was observed in proliferating SVZ progenitors (28). Another study showed in vivo 31: 1125-1129 (2017) that hypoxic insult increased proliferation in SVZ-derived neural progenitor cell cultures and also increased Pax6 expression in SVZ tissue (29). These findings suggest that the increasing density of HIF1α-IR cells was correlated with the induction of neurogenesis after hypoxia.…”
Section: Discussionmentioning
confidence: 94%
“…Pax6 expression was observed in proliferating SVZ progenitors (28). Another study showed in vivo 31: 1125-1129 (2017) that hypoxic insult increased proliferation in SVZ-derived neural progenitor cell cultures and also increased Pax6 expression in SVZ tissue (29). These findings suggest that the increasing density of HIF1α-IR cells was correlated with the induction of neurogenesis after hypoxia.…”
Section: Discussionmentioning
confidence: 94%
“…NPCs isolated from neonatal mice subjected to intermittent hypoxia exhibit increased proliferative potential when propagated as neurospheres, an effect of hypoxia mediated by HIF-1α (Ross et al, 2012). In contrast to Notch and NF-κB, it is unclear whether HIF-1 plays an important role in synaptic plasticity, although it was reported that inhibition or genetic knockdown of HIF-1α blocks the ability IGF-1 to enhance synaptic transmission in cultured hippocampal neurons (Huang et al, 2010).…”
Section: Notch/nf-κb/p53/hif-1α Axis In Neuronal Plasticity and Resilmentioning
confidence: 99%
“…Another limitation is that the detailed mechanisms by which this protocol elicit the observed changes is not completely understood, something which this group continues to explore. Prior work demonstrated that HIF1-alpha target genes, EPO and VEGF, appear to be involved in both expansion and morphological changes in these cells 11 . Further, this report outlined that changes in expansion, in particular, become more pronounced with increased time in culture.…”
Section: Administration Of Acute Intermittent Hypoxiamentioning
confidence: 99%
“…This group has significant experience with the administration of systemic IH, and has conducted extensive studies on the role of IH in respiratory plasticity [3][4][5][6][7] . This work, and the recent finding that chronic IH increased neurogenesis in the rodent CNS [8][9][10] , forms the basis for the exploration of acute in vivo hypoxia as a preconditioning stimulus (i.e., prior to tissue harvest) on the subsequent culture of neural stem/progenitor cells (NPCs) 11 . Remarkably, when mouse pups were exposed to a brief (<1 hr) period of acute intermittent hypoxia (AIH), cells that were harvested from the subventricular zone (SVZ) had significantly increased capacity for expansion as neurospheres or adherent monolayer cells.…”
Section: Introductionmentioning
confidence: 98%